Collective impact of conventional cardiovascular risk factors and coronary calcium score on clinical outcomes with or without statin therapy: The St Francis Heart Study. (December 2016) - Waheed, Salman; Pollack, Simcha; Roth, Marguerite; Reichek, Nathaniel; Guerci, Alan; Cao, Jie J.
Abstract: Background and aims: The efficacy of statin therapy remains unknown in patients eligible for statin therapy with and without elevated coronary calcium score (CAC). The study sought to evaluate how cardiovascular risk factors, expressed in terms of statin eligibility for primary prevention, and CAC modify clinical outcomes with and without statin therapy. Methods: We conducted a post-hoc analysis of the St. Francis Heart Study treatment trial, a double-blind, placebo-controlled randomized controlled trial of atorvastatin (20 mg), vitamin C (1 g), and vitamin E (1000 U) daily, versus placebos in 990 asymptomatic individuals with CAC ≥ 80th percentile for age and gender. Primary cardiovascular outcomes included non-fatal myocardial infarction or coronary death, coronary revascularization, stroke, and peripheral arterial revascularization. We further stratified the treatment and placebo groups by eligibility (eligible when statin indicated) for statin therapy based on 2013 ACC/AHA guidelines and based on CAC categories. Results: After a median follow-up of 4.8 years, cardiovascular events had occurred in 3.9% of the statin treated but not eligible, 4.6% of the untreated and not eligible, 8.9% of the treated and eligible and 13.4% of the untreated and eligible groups, respectively ( p <0.001). Low CAC (<100) occurred infrequently in statin eligible subjects (≤4%) and was associated with low 10-year event rate (<1 per 100 person-years). In contrast, high CAC (>300) occurred frequently in more than 35% of the statin not eligible subjects and was associated with a high 10-year event rate (≥17 per 100 person-years). Risk prediction improved significantly when both clinical risk profile and CAC score were combined (net reclassification index p  = 0.002). Conclusions: Under the current statin treatment guidelines a small number of statin eligible subjects with low CAC might not benefit from statin therapy within 5 years. However, the statin not eligible subjects with high CAC have high event rate attributing to loss of opportunity for effective primary prevention. Highlights: The benefit of statin therapy is best predicted combining statin eligibility according to ACC/AHA guidelines and CAC. Statin therapy based on clinical risk alone may lead to over treating many with low CAC with limited benefit from statins. Statin therapy based on CAC alone may lead to under treating those with intermediate CAC but high clinical risk. Coronary calcium testing provides improved prediction of statin benefit among individuals eligible for statin therapy.